Helical Packing Columns for Preventing Foam Formation: Experimental and Numerical Investigations - Osorio Nesme, Anuhar; Hohagen, Hans; Topic, Nikola; Thünnesen, Julian; Mobarak, Mohammad Mobarak; Lyu, Wenjing; Jahn, Alexander; Kim, Sedong; Delgado, Antonio (Chemical Engineering & Technology, 2022)
Unwanted foaming and liquid bridging inside structured packings have a negative effect on the pressure drop during thermal separation processes. A novel helical design of a packing column for preventing foaming is presented. The effective interfacial area is calculated by numerical simulations. Different designs are analyzed by varying geometrical parameters such as helix pitch, channel opening angle, and number of channels. Different F-factor values and liquid loads are evaluated. Packings with larger helix pitch exhibited lower pressure drop and reduced effective interfacial area. Smaller channel opening angles increased the pressure drop and promoted unstable flow conditions. The novel packings show lower effective interfacial area than existing structured packings, but no foaming was observed in a wide range of operating conditions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Foaming; Mass transfer; Packing columns; Pressure drop; Structured packing